Vulnerability assessment to flood hazards ofhouseholds in flood-prone areas of KaseseDistrict, Western Uganda - Yayiru Tibara; Hannington Wasswa; Henry Musoke Semakula (wiley, 2023)
The study evaluated the level of household vulnerability to flood hazards in Kasese Municipality, Kasese District, Uganda. The municipality is divided into three divisions (viz., Central, Bulembia, and Nyamwamba). The study utilized both secondary and primary data. Secondary data were obtained through an extensive literature review, and primary data were obtained through household survey. Seventy households were systematically randomly selected from each division. The study used an indicator-based methodology. The indicators under the different categories were broken down into different classes basing on their features. The indicators were then normalized, and weights were assigned to different indicators using principal component analysis (PCA). The variables normalized were multiplied with the weights assigned to develop the indices for the components of vulnerability. Indices of vulnerability were created at the home level and aggregated at the division level. A chi-squared test at a significance level of 5% was used to test for differences in the level of household vulnerability. The results revealed that the Nyamwamba division was most exposed whereas the Central division was least exposed to floods. The Central division was also found most sensitive whereas the Bulembia division was least sensitive to floods. The Central division had better capacity to cope with floods whereas the Bulembia division had the least capacity. The study further revealed a significant difference in the level of households' vulnerability across the divisions. However, overall, the Nyamwamba division was found most vulnerable and the Central division least vulnerable to floods. About 43.8% of the households in Kasese Municipality were found highly vulnerable to floods. To reduce the high levels of exposure, households nearer major flooding river should be relocated to safer places and restrict settlement in flood-prone areas. To reduce the high levels of sensitivity and enhance adaptive capacities, the local government and other stakeholders should give jobs/income-generating opportunities to enhance the income levels and savings of the households in the flood-prone areas. To reduce the high levels of vulnerability, government and other stakeholders should develop policies and allocate funds for disaster risk reduction and adequately respond to flood disasters at the lowest administrative units of villages and subcounties.
Keywords: adaptive capacity; exposure; floods; Uganda; vulnerability222